(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper I present the preparation of (Sb2o3) thin films using thermal evaporation in vacuum, procedure with different thickness (100 ,150 ,200 ,and 250) nm, by using ( hot plate) from Molybdenum matter at temperature in ( 9000c) and the period of time (15mint) ,the prepared in a manner thermal evaporation in a vacuum and precipitated on glass bases, pure Antimony Trioxide (sb2o3 ) thin films with various condition have been successfully deposited by (T.E.V) on glass slide substrates. The substrates temperature of about 100oC and the vacuum of about 10-6 torr, to investigated oxidation of evaporated, measure spectra for prepared films in arrange of wavelength (250 – 1100 nm). The following optical properties have been calculated: the absorption coefficient, the forbidden (Eg) for direct and indirect transitions "absorbance, refractive index, extinction coefficient, real and imaginary parts" of the dielectric constant.